Patient, family member, and ambulance staff experiences of prehospital acute pain management in adults: A systematic review and meta‐synthesis. Issue 2 (10th April 2023) - Whitley, Gregory Adam; Wijegoonewardene, Nimali; Nelson, David; Curtis, Ffion; Ortega, Marishona; Siriwardena, Aloysius Niroshan
Abstract: Background: We aimed to synthesize the qualitative experiences of patients, their family members, and ambulance staff involved in the prehospital management of acute pain in adults and generate recommendations to improve the quality of care. Methods: A systematic review was conducted following the enhancing transparency in reporting the synthesis of qualitative research (ENTREQ) guidelines. We searched from inception to June 2021: MEDLINE, CINAHL Complete, PsycINFO and Web of Science (search alerts were screened up to December 2021). Articles were eligible for inclusion if they reported qualitative data and were published in the English language. The Critical Appraisal Skills Program for qualitative studies checklist was used to assess risk of bias, thematic synthesis was performed on included studies and recommendations for clinical practice improvement were generated. Results: Twenty‐five articles were included in the review, representing over 464 patients, family members, and ambulance staff from 8 countries. Six analytical themes and several recommendations to improve clinical practice were generated. Strengthening the patient–clinician relationship by building trust, promoting patient empowerment, addressing patient needs and expectations, and providing a holistic approach to pain treatment is key to improving prehospital pain management in adults. Shared pain management guidelines and training across the prehospital and emergency department intersection should improve the patient journey. Conclusion: Interventions and guidelines that strengthen the patient‐clinician relationship and span the prehospital and emergency department phase of care are likely to improve the quality of care for adults suffering acute pain in the prehospital setting.